How socially selective is the German system of initial vocational education and training? : Transitions into initial vocational training and the influence of social background - Beicht, Ursula [Verfasser]; Walden, Günter [Verfasser] (My University, 2015)
"In Germany, social background has a strong influence on school performance in the general educational system. Children from lower social classes have fewer opportunities to gain higher school leaving certificates. In this paper, we ask the question if social selectivity is also present in the German system of vocational education and training. Based on the data-set of the German Transition Study of the Federal Institute of Vocational Education and Training, we analyse the transition from school to vocational education and training, including also the transition to higher education. We show that the successful placement in full vocational qualification programmes leading to a recognised occupation depends strongly on the general school-leaving certificate. As regards the direct influence of social background, there is some evidence for fewer chances for young people from lower social classes but only for non-holders of a higher education entrance qualification (HEEQ). Young people from lower social classes holding a HEEQ more often choose initial vocational training instead of a higher education degree. Our results show that the strong social selectivity of the German general educational system is perpetuated in the German system of vocational education and training and determines long-run career perspectives. Therefore, a policy for reduction of social selectivity in Germany has to target the teaching in the schools of general education." (Authors' abstract, BIBB-Doku)
Published online: 09 Dec 2014 (iFirst). Berücksichtigt in JB 2014.
Keywords: G 1.3.2.2.1 Erste Schwelle, in Ausbildung; G 1.3.2 Bildungsverhalten und -verläufe; P 2.1 Schulabgänger; Berufsausbildung; Duales System; Berufseinmündung; Erste Schwelle; Ausbildungschance; Bildungsverlauf; Schulabgänger; Verlaufsuntersuchung; Einflussfaktor; Soziale Faktoren; Schulabschluss; Beruflicher Status; Eltern; Bildungsabschluss; Geschlecht; Migrationshintergrund; Empirische Untersuchung; BIBB-Übergangsstudie